Economic Impact of Ecuador's Largest Christmas Tree on Entrepreneurship - Cuenca 2022 (Innovation & Development in Engineering and Applied Science, 2024)
Seasonal tourist attractions became a source of work and economic development, which is why entertainment spaces are created during the Christmas season. The objective of the study is to analyze the economic impact of the Largest Christmas Tree in Ecuador on the enterprises located in the Miraflores park in the city of Cuenca 2022. The methodology was quantitative and qualitative with descriptive and phenomenological scope, with a non-experimental research design. cross-sectional, to collect information a questionnaire was used applied to a population of 43 entrepreneurs and a simple random sample of 28 involved. The results reveal that the average daily income of the entrepreneurs is less than $300, while they have the same monthly income, but they earn payment amounts for basic services and taxes. In conclusion, the activities generated in the temporary attractions enhance domestic tourism and entrepreneurs benefit because their economic income is strengthened in the event of the largest Christmas tree in Ecuador.
Keywords: Tourist attractions; Economic strengthening; Entrepreneurship